Kultūros, dialogo ir keliautojo apmąstymai tarptautinėse studentų dirbtuvėse Florencijoje - Bankauskaitė, Gabija (Respectus Philologicus, 2018)
Do you enjoy traveling? Probably there is no person with a negative response. Some of travellers are fast collectors of famous places, while others are just observers of culture and lifestyle. The third ones simply lost in tourism gaining popularity on social networks, while some like to travel on a virtual basis... But let us just imagine positive tourism which really helps to preserve cultural and historical values. Why are some countries already protecting themselves form tourists? Finally, just ask yourself what kind of tourist are you? an active user? a philosophical custodian? a passive observer? The Romualdo Del Bianco Foundation (Fondazione Romualdo Del Bianco®) gives the answers to these and many other questions. The foundation cares about the values and responsibility of tourism philosophy. The International Institute Life Beyond Tourism® promotes the transformation of tourism into meaningful travel. It motivates the consumer of commercial tourism to reflect on the cultural and philosophical value of travel and traveler.I’d like to emphasize the goal of the Romualdo Del Bianco Foundation – an international integration of people from different cultures, countries and religions. The non-profit organization focuses on young people and believes they are more open to communication and knowledge of their peers’ traditions and culture in other countries. The Foundation maintains the international workshops for studentss in the city of Florence annually. Moreover, the one also organizes Intensive Training Courses for Trainers Life Beyond Tourism every year. Young people and teachers from all over the world are being invited to promote intercultural exchanges. The value of the beauty and versatility of various heritages relate to the power to promote cultural and personal exchanges of people. Students from different cultures can get acquainted, exchange knowledge and strengthen friendship through various meetings, exhibitions, concerts and other initiatives supported by the Fondation.Nowadays, in the globalization era, any attracting heritage is radically being changed. On the one hand, it is the result of the international tourism being maintained by business. On the other hand, a hasty tourist usually has no motivation to establish friendly relations with the residents. Therefore a city seeks for an income and only works for tourists, thus, the mutual exchange of local communities and tourism users is usually confined to trading. Due to this, the improperly organized tourism undermines local culture and pushes the community out of town. Consequently this has already happened in Venice, Madrid, and many other historical cities. That is why the Foundation organizes many annual events which aim is to encourage tourists to become temporary residents and slowly enjoy the unique and distinctive spirit of the Florentine art and culture.The 12th international students workshop took place at Florence on 5–12 November 2017. The organizers of the scientific event “Linguocultural Space of the City with Special Reference to Worl Famous People and Florentine Handicrafts” were the Foundation of Romualdo del Bianco, the International Institute Life Beyond Tourism® (Italy) and Ivanovo State University (Russia). The partners of project were University of Florence, Vilnius University, and Russian universities of Moscow and Kazan.The first day of activities, 6th of November, has coincided with the first Sunday of the month. According to the order of the Minister of Italian Heritage, Culture and Tourism, the museum admission is free of charge every first Sunday of the month throughout the country. Therefore the delegations had a great opportunity to visit several museums of Florence.Students and lecturers met on the second day at the Coppini Palace, where the Foundation was located. The visitors could visit the palace for free and look at the fondation collections of books and cultural souvenirs from all around the world. So, the event was opened by the founder Paolo Del Bianco. The participants were welcomed by the General Secretary of the Foundation Simone Giometti, and the leader of the International workshop professor Olga Karpova. Then the delegations presented their countries and universities. Afterwords the students discussed their homework – they introduced the activities of the local craftsmen from their cities. Finally, the lecturers highlighted future activities and assignments for students in the coming days of the workshop.At the afternoon session participants were invited to attend the lecture “Tools for Studying the History of Italian Language” by dr. Cosimo Burgas (Italian Science Council and Institute for Opera del Vocabolario Italiano in Florence). The speaker revealed the patterns of the formation of common Italian language and focused our attention on the main sources – the works by Dante Alighieri, Francesco Petrarca, and Giovanni Boccaccio.The 7th of November was devoted to the philosophy of Life Beyond Tourism®. The courses were delivered by Alesia Koush, a lecturer of the International Institute. The destructive and slow tourism, also the practical tasks were discussed actively.The participants of the students workshop were invited to the graceful Strozzi Palace on Wednesday. The director of the Scientific and Literary Vieusseux Cabinet (Gabinetto Vieusseux) dr. Laura Desideri underlined the uniqueness of this place. Actually the Cabinet was founded by the Protestant merchant Giovanni Pietro Vieusseux in 1819 in the Florence Library. It is important to mention that this place has played a very siginificant role to bringing Italian culture to the European countries in the 19th century and became one of the main points of the Renaissance movement. Forasmuch as a variety of the world and European periodicals have been being accumulated and stored there it has been a space for reading, discussing and excanging ideas for florentians and travelers for years. In fact, 42 scientific and literary journals were registered in the Cabinet in 1820. In addition to numerous publications in Italian, there should be mentioned the periodicals in English The Edinburgh Review, The Quarterly Review, in German Morgenblatt, in French Revue encyclopédique, Bibliothèque universelle, Nouvelles Annales des voyages de la géographie et de l’histoire, Annales des mines. Eventually almost 700 subscriptions were issued that year. Each visitor of the Cabinet had to write down his / her name, nationality, country of origin, hotel name, dates of stay, the title of the publication in the Visitor’s Book. After all a crowd of prominent people became the visitors of the cabinet once or more in the 19th century: Arthur Schopenhauer, Stendhal, Giacomo Leopardi, Henry W. Longfellow, James Fenimore Cooper, Hector Berlioz, Walter Scott, Ralph Waldo Emerson, August von Platen, Franz Liszt, Napoleone Giuseppe Carlo Bonaparte, John James Ruskin, William Makepeace Thackeray, Robert Browning, Théophile Gautier, Émile Zola, Vittorio Emanuele, Fyodor Dostoevsky, Mikhail Bakunin, Mark Twain, Aldous Huxley, Joseph Rudyard Kipling, and others. Therefore the records of the visitors have revealed a lot of secrets to the researchers – what languages were being used by the visitors while signing, what kind of nationalities they were from, where they came from, where they were staying, and what they had been reading. Summarizing, the lecture “Famous Russains at the Gabinetto Vieusseux in the Nineteenth Century” needs to be emphasized. It was delivered by dr. Laura Desideri and discovered a number of unknown facts about the places in Florence being visited of the famous artists, politicians and artists.Further the participants of the workshop visited the University of Florence and had a meeting with professor Marcello Garzaniti after lunch. They interacted with university students and shared the experience on the graduate writing methodology.The late afternoon was devoted to the specific project of the Institute of Life Beyond Tourism® Vo per Botteghe – free initiative Life Beyond Tourism in order to let to know the traditional crafts of Florence and raise the awareness towards the identity of territory. The participants of the workshop received temporary Florence passports and visited a few of the city craftsmen. The first, one of the oldest European cosmetics and spice manufacturers store, is located in the Santa Maria Novella Monastery. They visited the Francesco family at Giorni Bookstore, where one can buy very ancient and rare books, for example, the travel format of “Comedy” by Dante Alighieri, or Enzo Ferrari book with his signature. And the last visited place was the Riccer family ceramics store.Another day of the workshop was dedicated to the autonomous work of the groups in order to visit the Florentine Monuments with the project coordinators, since the visiting students were required to complete the tasks formulated by their curators at the begining of the event. Consequently, they were allowed to analyze the interfaces of linguocultural space of the city.On the sixth day, the participants of the workshop visited the Laurentian Library at San Lorenzo Square (Biblioteca Medicea Laurenziana). In fact, this library was designed and implemented by Michelangelo di Lodovico Buonarroti Simoni. This is the only non-religious work of this artist. Actually the library is one of the most important and most prestigious antique heritage centers in Italy. It stores nearly 11,000 manuscripts and about 4,500 early printed books. The Medici family had been the greatest patron of culture and art in Renaissance Florence for ages. The Medici had been accumulating and collecting manuscripts and books according to the criteria of quality and aesthetics. Thus, the library contains the unique manuscripts by Tacitus, Plinius, Aeschylus, Sophocles, Quintilianus, Virgilius, and other famous men.The final discussion of the project activities took place at Coppini Palace. The students presented the works they had done during the week, and the lecturers assessed them. The exhibition of the students’ works Workshop “Linguocultural space of the city with special reference to the dictionary project” – Florence in the works of world famous people was organized. Finally, the certificates were granted to all the participants and the official closing of the workshop occured.To sum up, the close cooperation ties have been established during the international workshop week between Vilnius University Kaunas Faculty and the Foundation, the International Institute Life Beyond Tourism®, and Ivanovo State University. The Memorandum of Cooperation between the Foundation and Vilnius University was signed in Florence on 3–4 March 2018 at the 20th General Assembly and International Symposium “Heritage for Planet Earth 2018”. Thus, lecturers and students of Vilnius university are invited to participate in the Foundation’s activities. Lecturers are invited to attend the courses and become Certified Trainers of the Life Beyond Tourism Movement at Vilnius university. The students and their lecturers are invited to participate in the 13th International Students Workshop in Florence on 5–11 November 2018. Undoubtedly, the purpose of the workshop is to develop more intensive cultural ties, while encouraging scientific and cultural cooperation between universities and research centers of the world in the linguocultural space of Florence.
Keywords: nėra